Enhanced emission of encaged-OH−-free Ca12(1−x)Sr12xAl14O33:0.1%Gd3+ conductive phosphors via tuning the encaged-electron concentration for low-voltage FEDs. Issue 20 (29th March 2017) - Zhang, Meng; Liu, Yuxue; Yang, Jian; Zhu, Hancheng; Yan, Duanting; Zhang, Xinyang; Liu, Chunguang; Xu, Changshan; Zhang, Hong
Abstract : This research reported the electrical, magnetic and optical properties of encaged-OH − -free Ca12(1− x ) Sr12 x Al14 O33 :0.1%Gd 3+ conductive phosphors. Abstract : Encaged-OH − -free Ca12(1− x ) Sr12 x Al14 O33 :0.1%Gd 3+ conductive phosphors were prepared through a melt-solidification process in combination with a subsequent heat treatment. Absorption spectra showed that the maximum encaged-electron concentration was increased to 1.08 × 10 21 cm −3 through optimizing the doping amount of Sr 2+ ( x = 0.005). Meanwhile, FTIR and Raman spectra indicated that pure Ca11.94 Sr0.06 Al14 O33 :0.1%Gd 3+ conductive phosphor without encaged OH − and C2 2− anions was acquired. For the conductive powders heat-treated in air for different times, the encaged-electron concentrations were tuned from 1.02 × 10 21 to 8.3 × 10 20 cm −3 . ESR, photoluminescence, and luminescence kinetics analyses indicated that the emission at 312 nm mainly originated from Gd 3+ ions surrounded by encaged O 2− anions, while Gd 3+ ions surrounded by encaged electrons had a negative contribution to the UV emission due to the existence of an energy transfer process. Under low-voltage electron-beam excitation (3 kV), enhanced cathodoluminescence (CL) of the conductive phosphors could be achieved by tuning the encaged-electron concentrations. In particular, for the encaged-OH − -free conductive phosphor, the emission intensity of the CL was about one order of magnitude higher than that of the conductive phosphor containing encaged OH − anions. Our results suggested that the encaged-OH − -free conductive phosphors have potential application in low-voltage FEDs.